A cross sectional study to assess the discrimination faced by trans genders in health care facilities- Chennai, Tamil Nadu - A., Chitra; G. M., Sakthimarieswari; S., Kaleeswaran; V. R., Indhira; Pathiyil, Mythili Menon; ., Shreyavarshini (International Journal Of Community Medicine And Public Health, 2018)
Background: Transgender people are those who by definition, have a gender identity or gender expression that differs from their assigned sex at birth. The Government of Tamil Nadu was the first Indian state to pioneer welfare schemes for transgenders such as formation of transgender welfare board, creation of a third column for gender in college application forms. The study aims to assess the discrimination faced by the transgenders in health care facilities. Methods: A cross sectional study was carried out among 50 transgenders using a self-administered questionnaire. Results: Among 47 responendents, 17.6% of the transgenders had delayed going to hospital fearing discrimination. Harassment either in physical or verbal form experienced by 41.2% and 37.5% faced discrimination in form of judgemental looks or comments, while 5.9% of the transgenders were denied treatment altogether in the hospital. Denial of equal treatment experienced by 52.9% of the study participants. Conclusions: The study highlights that transgenders even today face considerable discrimination which refrains them from assessing health care facilities. Even though we in Tamil Nadu have pioneered with the formation of transgender board, free sex re-assignment surgery in government health care facilities, the utilisation by the transgenders are far from behind. This may be attributed due to the discrimination faced by the transgenders.